2021
DOI: 10.1016/j.artd.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Total Hip Arthroplasty Via the Direct Anterior vs Alternative Approaches for Acute Femoral Neck Fractures

Abstract: Background Total hip arthroplasty (THA) performed for displaced femoral neck fractures (FNF) is becoming a more frequent treatment in the active elderly population. The complication profiles associated with THA surgical approaches in the fracture setting are unclear. The purpose of this study was to compare a series of THA for FNF performed via the direct anterior (DA) approach vs alternative approaches (anterolateral and posterolateral). Methods A retrospective review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The length of hospital stay was significantly shorter with the anterior approach than with the posterior approach, and better results were attributed to earlier ambulation and rehabilitation. 28 In this study, periprosthetic fractures due to falls were observed in 2 patients after surgery: 1 occurred at 3 weeks post-surgery, and the other occurred at 5 months postsurgery. These patients required reoperation.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The length of hospital stay was significantly shorter with the anterior approach than with the posterior approach, and better results were attributed to earlier ambulation and rehabilitation. 28 In this study, periprosthetic fractures due to falls were observed in 2 patients after surgery: 1 occurred at 3 weeks post-surgery, and the other occurred at 5 months postsurgery. These patients required reoperation.…”
Section: Discussionmentioning
confidence: 64%
“…The length of hospital stay was significantly shorter with the anterior approach than with the posterior approach, and better results were attributed to earlier ambulation and rehabilitation. 28 …”
Section: Discussionmentioning
confidence: 99%
“…The use of the direct anterior approach (DAA) for primary and revision total hip arthroplasty (THA) has increased over recent years (Patel, Shah, and Erens 2019). DAA-THA has been associated with a lower risk of dislocation and revision due to instability, shorter hospital length of stay, and early postoperative function compared to posterior-based approaches (Singh et al 2020;Bendich et al 2021;Charney et al 2020;Kurkis et al 2021;Ponzio et al 2018;Elstad et al 2021). However, an increase in wound complications has been demonstrated following DAA-THA, likely due to increased exposure to anatomical bacterial reservoirs compared to the direct lateral (DL) and posterior approaches (PA) (Kurkis et al 2021;Purcell et al 2018;Shohat et al 2021).…”
Section: Introductionmentioning
confidence: 99%